Perovskite solar cell and preparation method thereof

By adding conjugated linoleic acid and/or its oligopolymerized derivatives to the perovskite precursor solution, the active layer of perovskite solar cells is prepared, which solves the problem of insufficient wet stability and light stability of perovskite solar cells, achieving higher stability and energy conversion efficiency, while reducing the preparation cost.

CN119836195APending Publication Date: 2025-04-15旗滨新能源发展(深圳)有限责任公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411993689.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Perovskite solar cells have insufficient wet stability and light stability, and the prior art solutions are complex and costly, and have a negative impact on battery performance.

Method used

Conjugated linoleic acid and/or its oligopolymerized derivative are added to the perovskite precursor solution, and the perovskite active layer is prepared by spin coating technology and annealed to improve the wet stability and light stability of perovskite solar cells.

Benefits of technology

By adding conjugated linoleic acid and/or its oligopolymerized derivative, the wet stability and light stability of perovskite solar cells are significantly improved, and their energy conversion efficiency is enhanced while reducing the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836195A_ABST
    Figure CN119836195A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite solar cell and a preparation method thereof, and belongs to the technical field of perovskite solar cells. Conjugated linoleic acid and / or a conjugated linoleic acid low-polymerization-degree derivative and a perovskite material are dissolved in a solvent to obtain a perovskite precursor solution, and the perovskite precursor solution is coated on the surface of a substrate to prepare a perovskite active layer, so that the wet stability and the light stability of the perovskite solar cell are improved; the chemical composition or structure of the perovskite material does not need to be changed by using a complex synthesis process, and expensive raw materials do not need to be introduced, so that the preparation cost can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to a perovskite solar cell and a preparation method thereof. Background Art

[0002] Solar cells are clean energy devices that convert solar energy directly into electrical energy. Perovskite solar cells have attracted widespread attention due to their high efficiency and low cost. However, the stability of perovskite solar cells, especially moisture stability and light stability, is an important challenge for their commercial application. The moisture stability problem is mainly due to the fact that perovskite materials are prone to degradation in a humid environment, resulting in a decrease in battery performance. The light stability problem is due to the fact that perovskite materials are prone to photocorrosion under light, which also affects the performance and life of the battery. Solutions of the prior art: In order to solve these problems, researchers have proposed some solutions. For example, by changing the chemical composition or structure of the perovskite material, or by adding specific additives to improve its stability. However, these methods often require complex synthesis processes or expensive raw materials, and may have a negative impact on other properties of the battery. Problems with the prior art: Although the prior art has made certain progress, there are still some problems and shortcomings.

[0003] First, existing stabilizers may have a negative impact on the photoelectric conversion efficiency of perovskite solar cells. Second, existing stabilization methods often require high-temperature treatment or long reaction times, which not only increases the complexity and cost of the preparation process, but may also damage the crystal structure of the perovskite material. Finally, existing stabilization methods have limited effects on improving the wet stability and light stability of perovskite solar cells, and still cannot meet the needs of practical applications. Summary of the invention

[0004] The main purpose of the present invention is to provide a perovskite solar cell and a preparation method thereof, so as to solve the technical problem that it is difficult to improve the moisture stability and light stability of the perovskite solar cell.

[0005] To achieve the above object, the present invention provides a method for preparing a perovskite solar cell, comprising the following steps:

[0006] Dissolving conjugated linoleic acid and / or conjugated linoleic acid low-polymerization-degree derivatives and perovskite materials in a solvent to obtain a perovskite precursor solution,

[0007] The perovskite precursor solution is coated on the surface of the substrate to prepare the perovskite active layer.

[0008] In some embodiments of the present invention, the perovskite precursor solution includes the conjugated linoleic acid low-polymerization degree derivative, and the degree of polymerization of the conjugated linoleic acid low-polymerization degree derivative is less than or equal to 300.

[0009] In some embodiments of the present invention, the added amount of conjugated linoleic acid and / or conjugated linoleic acid low-polymerization degree derivative in the solvent is (5-20) μL / mL.

[0010] In some embodiments of the present invention, in the step of preparing the perovskite active layer, the perovskite precursor solution is spin-coated onto the surface of the substrate, the spin-coating speed is 1000 rpm to 5000 rpm, and the spin-coating time is 10s to 30s.

[0011] In some embodiments of the present invention, the perovskite precursor solution is further annealed after being coated on the surface of the substrate.

[0012] In some embodiments of the present invention, the annealing temperature is 100° C. to 105° C., and the annealing time is 20 min to 40 min.

[0013] In some embodiments of the present invention, the substrate comprises an electron transport layer, and a perovskite active layer is prepared on the surface of the electron transport layer.

[0014] In some embodiments of the present invention, the substrate includes a hole transport layer, and a perovskite active layer is prepared on the surface of the hole transport layer.

[0015] The present invention also provides a perovskite solar cell prepared by the method for preparing a perovskite solar cell as described above.

[0016] In some embodiments of the present invention, the perovskite solar cell comprises, from bottom to top, a transparent conductive oxide layer, an electron transport layer, a perovskite active layer prepared by the preparation method of the present invention as described above, a hole transport layer and a metal back electrode; or,

[0017] The perovskite solar cell comprises, from bottom to top, a transparent conductive oxide layer, a hole transport layer, a perovskite active layer prepared as above by the present invention, an electron transport layer and a metal back electrode.

[0018] The beneficial effects that can be achieved by the present invention are:

[0019] The present invention adds conjugated linoleic acid and / or a conjugated linoleic acid low-polymerization-degree derivative to a perovskite precursor solution. The conjugated linoleic acid and / or a conjugated linoleic acid low-polymerization-degree derivative is a long carbon chain organic molecule with good hydrophobicity, and can effectively improve the wet stability of the perovskite solar cell. The low-polymerization-degree derivative of conjugated linoleic acid can also in-situ passivate the grain boundaries of the perovskite film, thereby improving the light stability and energy conversion efficiency of the perovskite solar cell. The conjugated linoleic acid itself has the cross-linking property initiated by light and heat, and can generate conjugated linoleic acid oligomers with a certain degree of polymerization under light or heating conditions, that is, the low-polymerization-degree derivative of conjugated linoleic acid, thereby in-situ passivating the grain boundaries of the perovskite film, thereby improving the light stability and energy conversion efficiency of the perovskite solar cell.

[0020] The present invention improves the moisture stability and light stability of perovskite solar cells by adding conjugated linoleic acid and / or conjugated linoleic acid low-polymerization degree derivatives to the perovskite precursor solution. There is no need to use a complex synthesis process to change the chemical composition or structure of the perovskite material, and there is no need to introduce expensive raw materials, which can reduce the preparation cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0022] Figure 1 It is a comparison diagram of the current density-voltage (JV) curves of the perovskite solar cells of Example 1 of the present invention and Comparative Example 1.

[0023] Figure 2 It is a comparison diagram of the current density-voltage (JV) curves of the perovskite solar cells of Example 2 of the present invention and Comparative Example 2.

[0024] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0025] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0028] The present invention provides a method for preparing a perovskite solar cell, comprising the following steps:

[0029] Dissolving conjugated linoleic acid and / or conjugated linoleic acid low-polymerization-degree derivatives and perovskite materials in a solvent to obtain a perovskite precursor solution,

[0030] The perovskite precursor solution is coated on the surface of the substrate to prepare the perovskite active layer.

[0031] The conjugated linoleic acid low-polymerization degree derivative of the present invention can be obtained by polymerizing conjugated linoleic acid molecules. Dissolving conjugated linoleic acid and / or conjugated linoleic acid low-polymerization degree derivative and perovskite material in a solvent to obtain a perovskite precursor solution can be understood as adding only conjugated linoleic acid or conjugated linoleic acid low-polymerization degree derivative, or adding both conjugated linoleic acid and conjugated linoleic acid low-polymerization degree derivative.

[0032] Conjugated linoleic acid and conjugated linoleic acid low-polymerization derivatives are explained below.

[0033] Conjugated linoleic acid is abbreviated as CLA, and its molecular formula is C 17 H 31 COOH. The double bonds of conjugated linoleic acid can be located at positions 7 and 9, 8 and 10, 9 and 11, 10 and 12, 11 and 13, 12 and 14, and each double bond has two conformations: cis (cis or c) and trans (trans or t).

[0034] The abbreviation of the low-polymerization-degree derivative of conjugated linoleic acid is oligo-CLA, which is a conjugated linoleic acid derivative formed by a polymerization reaction between conjugated linoleic acid molecules, and the polymerization reaction conditions include light conditions and / or heat conditions.

[0035] The present invention adds conjugated linoleic acid and / or a conjugated linoleic acid low-polymerization-degree derivative to a perovskite precursor solution. The conjugated linoleic acid and / or a conjugated linoleic acid low-polymerization-degree derivative is a long carbon chain organic molecule with good hydrophobicity, and can effectively improve the wet stability of the perovskite solar cell. The low-polymerization-degree derivative of conjugated linoleic acid can also in-situ passivate the grain boundaries of the perovskite film, thereby improving the light stability and energy conversion efficiency of the perovskite solar cell. The conjugated linoleic acid itself has the cross-linking property initiated by light and heat, and is used to prepare the perovskite film. Under light or heating conditions, conjugated linoleic acid oligomers with a certain degree of polymerization, namely, the low-polymerization-degree derivative of conjugated linoleic acid, can be generated, thereby in-situ passivating the grain boundaries of the perovskite film, thereby improving the light stability and energy conversion efficiency of the perovskite solar cell.

[0036] The present invention improves the moisture stability and light stability of perovskite solar cells by adding conjugated linoleic acid and / or conjugated linoleic acid low-polymerization degree derivatives to the perovskite precursor solution. There is no need to use a complex synthesis process to change the chemical composition or structure of the perovskite material, and there is no need to introduce expensive raw materials, which can reduce the preparation cost.

[0037] In some embodiments, the degree of polymerization of the low-polymerization degree derivative of conjugated linoleic acid is less than or equal to 300. For example, the degree of polymerization can be any value in the range of 300 to 50: 50, 100, 150, 200, 250, 300, etc. Within the above degree of polymerization range, the low-polymerization degree derivative of conjugated linoleic acid has a suitable viscosity, which is convenient for determining the addition amount.

[0038] In some embodiments, the concentration of conjugated linoleic acid and / or conjugated linoleic acid low-polymerization degree derivatives in the solvent is (5 to 20) μL / mL. For example, in 1 mL of solvent, 5 μL, 6 μL, 7 μL, 8 μL, 10 μL, 12 μL, 15 μL, 16 μL, 17 μL, 18 μL, 20 μL, etc. of conjugated linoleic acid and / or conjugated linoleic acid low-polymerization degree derivatives can be added to improve the light stability and moisture stability of perovskite solar cells.

[0039] In the present invention, the perovskite material and the solvent may be selected from those commonly used in the art.

[0040] In the present invention, the perovskite material comprises an ABX3 structure, wherein the A position is an organic cation, the B position is a metal ion, including lead (Pb) or tin (Sn), etc., and the X position is a halogen anion, including iodine (I), bromine (Br) or chlorine (Cl), etc. In some embodiments, the perovskite material comprises at least one of lead methylamine iodide, lead methylamine bromide, and lead methylamine iodide bromide. The present invention does not require the structure of the perovskite material to be modified, and the purpose of improving the wet stability and light stability of the perovskite solar cell can be achieved by simply adding conjugated linoleic acid and / or a low-polymerization derivative of conjugated linoleic acid.

[0041] In some embodiments, the solvent includes at least one of dimethylformamide, dimethyl sulfoxide, and N-methyl-2-pyrrolidone. The above types of solvents can not only disperse the perovskite material well, but also dissolve the conjugated linoleic acid and the low-polymerization degree derivative of conjugated linoleic acid well, so as to obtain a uniform perovskite precursor solution, which is conducive to preparing a uniform thin film perovskite active layer.

[0042] In some embodiments, the perovskite precursor solution is prepared as follows: weigh the perovskite material and conjugated linoleic acid and / or a low-polymerization degree derivative of conjugated linoleic acid, dissolve them in a solvent, and stir them evenly.

[0043] In some embodiments, the solvent includes a mixed solution of anhydrous N,N-dimethylformamide and anhydrous dimethyl sulfoxide, and the volume ratio of anhydrous N,N-dimethylformamide to anhydrous dimethyl sulfoxide is 8:1.

[0044] In some embodiments, a vortex oscillator is used to promote the dissolution of the perovskite material and conjugated linoleic acid and / or conjugated linoleic acid low-polymerization derivatives. The oscillation time can be determined according to the added amount to promote the dissolution of the perovskite material and conjugated linoleic acid, for example, 2 hours.

[0045] In some embodiments, a one-step method can be used to prepare a perovskite active layer. For example, a perovskite precursor solution is spin-coated onto the surface of a substrate at a spin-coating speed of 1000 rpm to 5000 rpm; the spin-coating time is 10s to 30s. In one embodiment, the spin-coating includes a primary spin-coating and a secondary spin-coating, the primary spin-coating speed is 1000 rpm, the spin-coating time is 10s, the secondary spin-coating speed is 5000 rpm, the spin-coating time is 30s, and an anti-solvent is added dropwise at the 20th second of the secondary spin-coating, and the anti-solvent includes anhydrous chlorobenzene.

[0046] In some embodiments, after the spin coating is completed, an annealing treatment is performed, the annealing temperature is 100° C. to 105° C., and the annealing time is 20 min to 40 min, and can be 30 min.

[0047] The preparation method of the perovskite solar cell of the present invention improves the preparation process of the perovskite active layer, and is applicable to the preparation of the normal perovskite solar cell and the inverted perovskite solar cell. Therefore, the substrate includes a semi-finished perovskite solar cell.

[0048] Exemplarily, the perovskite solar cell is an upright perovskite solar cell, the substrate includes a transparent oxide glass and an electron transport layer formed on the surface of the transparent oxide glass, and a perovskite active layer is prepared on the surface of the electron transport layer. In some embodiments, an interface modification layer commonly used in the art can also be prepared on the surface of the electron transport layer to improve the contact between the electron transport layer and the perovskite active layer. In this embodiment, the perovskite active layer is prepared on the surface of the interface modification layer.

[0049] Exemplarily, the perovskite solar cell is an inverted perovskite solar cell, the substrate includes a transparent oxide glass and a hole transport layer formed on the surface of the transparent oxide glass, and a perovskite active layer is prepared on the surface of the hole transport layer. In some embodiments, an interface modification layer commonly used in the art can also be prepared on the surface of the hole transport layer to improve the contact between the hole transport layer and the perovskite active layer. In this embodiment, the perovskite active layer is prepared on the surface of the interface modification layer.

[0050] The perovskite solar cell of the present invention includes an upright perovskite solar cell and an inverted perovskite solar cell.

[0051] When the perovskite solar cell is an upright perovskite solar cell, the perovskite solar cell includes, from bottom to top, a transparent conductive oxide layer, a hole transport layer, a perovskite active layer prepared according to the preparation method of the present invention, an electron transport layer and a metal electrode.

[0052] When the perovskite solar cell is an inverted perovskite solar cell, the perovskite solar cell includes, from bottom to top, a transparent conductive oxide layer, an electron transport layer, a perovskite active layer prepared according to the preparation method of the present invention, a hole transport layer and a metal electrode.

[0053] Therefore, in some embodiments, the method for preparing a perovskite solar cell further includes the steps of preparing a transparent conductive oxide layer, preparing an electron transport layer, a hole transport layer, and a metal electrode. The above functional layers can be prepared by referring to the commonly used technical means in the art.

[0054] Exemplarily, the steps for preparing the transparent conductive oxide layer are as follows: the transparent conductive oxide glass is cleaned in alkaline detergent, pure water, ethanol, and isopropanol solutions in sequence, then blown dry with a nitrogen air gun, and then treated with ultraviolet ozone (UVO). The surface can also be treated with oxygen plasma to enhance the wettability of the transparent conductive oxide glass surface.

[0055] Exemplarily, the preparation steps of the electron transport layer are as follows: use a commercial Alfa Aesar SnO2 nanoparticle dispersion (aqueous solution with a mass fraction of 15%), dilute it in ultrapure water at a volume ratio of 1:5 to obtain an electron transport layer precursor solution; place the transparent conductive oxide glass on a uniform gel spin coater, take 50μL to 200μL of the electron transport layer precursor solution with a pipette, drop it on the transparent conductive oxide glass, and spin coat it at a speed of 3000rpm to 5000rpm and an acceleration of 3000rpm / s to 5000rpm / s for 15s to 60s. After the spin coating is completed, the transparent conductive oxide glass is immediately placed on a heating table for annealing, the annealing temperature is 130℃ to 180℃, and the annealing time is 15min to 60min. This step can be prepared in an air environment with a humidity range of 0-80%RH, without the need for a glove box, and can be prepared directly in a fume hood.

[0056] Exemplarily, a homemade sol-gel solution can also be used to prepare the electron transport layer. The electron transport layer precursor solution is prepared as follows: weigh 10mg to 40mg of SnCl2·2H2O, then dissolve it in 1ml of anhydrous ethanol, add a magnet and stir it on a magnetic stirrer at room temperature to accelerate the dissolution to form a SnO2 nanoparticle solution. Spin coating is performed at a speed of 3000rpm to 5000rpm and an acceleration of 3000rpm / s to 5000rpm / s for 15s to 60s. After annealing at 110°C for 10min, transfer to a 200°C hot stage and continue annealing for 60min. This step can be prepared in an air environment with a humidity range of 0-80% RH, without the need for a glove box, and can be prepared directly in a fume hood.

[0057] Exemplarily, the preparation steps of the hole transport layer are as follows: Spiro-OMeTAD, lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI), 4-tert-butylpyridine (TBP) and chlorobenzene solvent are mixed to form a hole transport layer precursor solution, and 50 μL to 200 μL of the hole transport layer precursor solution is dripped on the surface of the substrate using a pipette, the spin coating speed is set to 3000 rpm to 6000 rpm, the spin coating time is set to 15s to 60s, and the spin coating acceleration is set to 1000rpm / s to 6000rpm / s.

[0058] In some embodiments, if Spiro-OMeTAD material is used as a hole transport layer, it needs to be placed in dry air for oxidation, and the oxidation time takes 1 to 2 days. Here, the solution preparation can add cobalt salt materials that accelerate the oxidation of Spiro-OMeTAD, such as commercial cobalt (III) complex (FK209) materials, to shorten the oxidation time.

[0059] Exemplarily, the steps for preparing the metal electrode are as follows: a 50nm to 120nm metal electrode is deposited in a thermal evaporation coating machine, and the metal material can be a conductive metal material such as gold or silver.

[0060] In some embodiments, in order to passivate the defects of the perovskite film, the preparation method of the perovskite solar cell further includes the preparation of a passivation layer, which can be prepared by referring to common means in the art. Exemplarily, a layer of passivation layer material can be used on the upper interface, such as phenethylammonium iodide (PEAI), octylammonium iodide (OAI), benzylammonium iodide (PMAI), benzamidine hydrochloride (PFACl), benzylamine hydrochloride (PMACl), etc. One or more mixtures to obtain a passivation layer precursor solution, and then the passivation layer precursor solution is spin-coated on the surface of the perovskite absorption layer of the substrate to obtain a passivation layer.

[0061] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0062] Example 1

[0063] Example 1 The preparation method of the perovskite solar cell is as follows:

[0064] Preparation of transparent conductive oxide glass

[0065] The etched patterned FTO glass was placed in an anionic surfactant solution, deionized water, ethanol and isopropanol for ultrasonic cleaning for 15 minutes respectively. After cleaning, it was blown dry with a nitrogen flow for later use.

[0066] Deposition of electron transport layer

[0067] A commercial SnO2 colloidal dispersion and deionized water were mixed in a volume ratio of 1:3, and ultrasonically treated in an ultrasonic cleaning machine to obtain a SnO2 solution.

[0068] The cleaned FTO glass was placed in a UV ozone treatment machine and treated with ozone for 20 minutes. Then, an electron transport layer was prepared on the surface of the FTO glass by static spin coating in an air atmosphere. The rotation speed was 3000 rpm, the spin coating time was 30 seconds, and the spin coating amount was 100 μL. After the spin coating, it was annealed at 150°C for 30 minutes to form a SnO2 electron transport layer.

[0069] Deposition of the perovskite active layer

[0070] Accurately weigh a mixture of 19.5 mg of CsI, 15.9 mg of RbI, 8.4 mg of MABr, 219.5 mg of FAI, 656.9 mg of PbI2 and 27.5 mg of PbBr2 powders, then add 18 μL of conjugated linoleic acid (CLA) and 1 mL of anhydrous DMF / DMSO mixed solvent (v:v=4:1), and oscillate on a vortex oscillator for 2 h to completely dissolve it to obtain a perovskite precursor solution, the concentration of which is 1.5 M.

[0071] A one-step method was used to prepare the perovskite film, and anhydrous chlorobenzene was used as the anti-solvent. Specifically, the FTO glass deposited with the SnO2 electron transport layer was placed in a UV ozone treatment machine and treated with ozone for 20 minutes. In a glove box with a nitrogen atmosphere, 70 μL of the perovskite precursor solution was spin-coated on the SnO2 electron transport layer. The spin coating was divided into two processes, with specific parameters of 1000 rpm, 10s and 3000 rpm, 30s, and 150 μL of anhydrous chlorobenzene was quickly added at 15s in the second process. After the spin coating, the film was annealed at 100°C for 30 minutes to form a perovskite active layer.

[0072] Deposition of passivation layer

[0073] 15 mg of 2-phenylethylamine hydroiodide (PEAI) was accurately weighed and dissolved in 3 mL of anhydrous isopropanol, and the passivation layer precursor solution was obtained by oscillating on an oscillator to mix well. In a glove box with a nitrogen atmosphere, 100 μL of the passivation layer precursor solution was statically spin-coated on the surface of the perovskite active layer at a spin-coating speed of 5000 rpm for 30 s. After the spin-coating process, no further annealing treatment was required, and the subsequent hole transport layer deposition was directly carried out.

[0074] Deposition of hole transport layer

[0075] Accurately weigh 90 mg of Spiro-OMeTAD, add 44 μL of bis(trifluoromethane)sulfonyl imide lithium salt (LiTFSI) stock solution (260 mg Li-TFSI dissolved in 1 ml anhydrous acetonitrile), 37 μL tBP (4-tert-butylpyridine) and 1 mL anhydrous chlorobenzene, and mix by ultrasonic treatment for 5 min to obtain a hole transport layer precursor solution. In a glove box with a nitrogen atmosphere, 60 μL of the hole transport layer precursor solution was dynamically spin-coated on the passivation layer film at a spin-coating speed of 2000 rpm and a spin-coating time of 30 s. No annealing treatment was required.

[0076] Deposition of metal back electrode

[0077] The FTO glass prepared with the hole transport layer is de-edged and placed in a vacuum coating machine, and a 100nm Ag electrode is evaporated on it, finally obtaining a complete perovskite solar cell device.

[0078] Example 2

[0079] Example 2 A perovskite solar cell was prepared by the preparation method of Example 1, but the difference was that in the step of preparing the perovskite active layer, the preparation of the perovskite precursor solution was different, specifically as follows: accurately weigh 705.3 mg of PbI2, 240.8 mg of FAI, 29.7 mg of MACl and 5.9 mg of MAPbBr3 powder mixture, and then add 18 μL of conjugated linoleic acid (CLA) and 1 mL of anhydrous DMF / DMSO mixed solvent (v:v=8:1), and oscillate on a vortex oscillator for 2 h to completely dissolve it to obtain a perovskite precursor solution, the concentration of the precursor solution was 1.53 M.

[0080] Example 3

[0081] Example 3 A perovskite solar cell was prepared by referring to Example 1, but the difference was that the amount of CLA contained in the perovskite precursor solution of Example 3 was different:

[0082] The amount of CLA contained in the perovskite precursor solution of Example 3 is 5 μL.

[0083] Example 4

[0084] Example 4 A perovskite solar cell was prepared by referring to Example 1, but the difference was that the amount of CLA contained in the perovskite precursor solution of Example 4 was different:

[0085] The amount of CLA contained in the perovskite precursor solution of Example 4 is 20 μL.

[0086] Example 5

[0087] Example 5 A perovskite solar cell was prepared by referring to Example 2, but the difference was that the amount of CLA contained in the perovskite precursor solution of Example 5 was different:

[0088] The amount of CLA contained in the perovskite precursor solution in Example 5 is 5 μL.

[0089] Example 6

[0090] Example 6 A perovskite solar cell was prepared by referring to Example 2, but the difference was that the amount of CLA contained in the perovskite precursor solution of Example 6 was different:

[0091] The amount of CLA contained in the perovskite precursor solution of Example 6 is 20 μL.

[0092] Comparative Example 1

[0093] Comparative Example 1 A perovskite solar cell was prepared by referring to the preparation method of Example 1, except that CLA was not added when preparing the perovskite active layer.

[0094] Comparative Example 2

[0095] Comparative Example 2 A perovskite solar cell was prepared by referring to the preparation method of Example 2, except that CLA was not added when preparing the perovskite active layer.

[0096] Performance Testing

[0097] 1. Determine the efficiency of the perovskite solar cell devices obtained in Examples 1 to 6 and Comparative Examples 1 to 2 after being stored for different periods of time.

[0098] 2. Determine the Voc open circuit voltage (V), Jsc short circuit current density (mA / cm2) of the perovskite solar cell devices obtained in Examples 1 to 6 and Comparative Examples 1 to 2. 2 ), FF filling factor (mA / cm 2 ), PCE photoelectric conversion efficiency (%). The results are shown in Table 2. In addition, Figure 1 1 is a comparison diagram of the current density-voltage (JV) curves of the perovskite solar cells of Example 1 of the present invention and Comparative Example 1, Figure 2 It is a comparison diagram of the current density-voltage (JV) curves of the perovskite solar cells of Example 2 of the present invention and Comparative Example 2.

[0099] Table 1 Efficiency of perovskite solar cells obtained in the examples and comparative examples at different storage times

[0100]

[0101]

[0102] Table 2 Performance comparison of perovskite solar cells obtained in the examples and comparative examples

[0103]

[0104] It can be seen from Table 1 that in the comparison of the placement stability of the devices of Example 1 and Comparative Example 1 under the condition of relative humidity of 35%-45%, the device of Example 1 still maintained more than 95% of the initial efficiency after 7 days of storage, and the efficiency of the device of Comparative Example 1 decayed to less than 80% of the initial efficiency. In the comparison of the placement stability of the devices of Example 2 and Comparative Example 2 under the condition of relative humidity of 35%-45%, the device of Example 2 still maintained more than 95% of the initial efficiency after 7 days of storage, and the efficiency of the device of Comparative Example 2 decayed to less than 80% of the initial efficiency. Moreover, the perovskite devices obtained in Examples 3 to 6 all achieved good stability. It can be seen that the devices obtained by adding CLA to the perovskite precursor solution to prepare the perovskite active layer achieved good stability.

[0105] The power conversion efficiency (PCE) of the device of Example 1 is 23.22%, the open circuit voltage (Voc) is 1.158V, and the short circuit current density (Jsc) is 24.921mA / cm 2 , FF is 80.465%. In comparison, the PCE of the device in comparative example 1 is 22.12%, Voc is 1.148V, and Jsc is 24.799mA / cm 2 , FF is 77.699%, and the photoelectric conversion efficiency of the device is significantly improved from 22.12% to 23.21%, indicating that the addition of CLA in the perovskite precursor solution has the effect of in-situ passivation of the grain boundaries of the perovskite film, thereby improving the energy conversion efficiency of the perovskite solar cell. Similarly, the power conversion efficiency (PCE) of the device in Example 2 is 23.91%, the open circuit voltage (Voc) is 1.156V, the short circuit current density (Jsc) is 25.370mA / cm2, and the FF is 81.538%. In contrast, the PCE of the device in Comparative Example 2 is 22.70%, the Voc is 1.147V, and the Jsc is 25.310mA / cm 2 , FF is 78.206%, and the photoelectric conversion efficiency of the device is significantly improved from 22.70% to 23.91%, indicating that the addition of CLA in the precursor solution has the effect of in-situ passivation of the grain boundaries of the perovskite film, thereby improving the energy conversion efficiency of the perovskite solar cell. In addition, the perovskite solar cells of Examples 3 to 6 also achieved good photoelectric conversion efficiency.

[0106] From Table 1 and Table 2, it can be seen that the present invention adds conjugated linoleic acid to the perovskite precursor solution. Conjugated linoleic acid has good hydrophobicity due to the long carbon chain organic molecule, which can effectively improve the wet stability of the perovskite solar cell. Moreover, conjugated linoleic acid has light- and heat-induced cross-linking properties, and can produce conjugated linoleic acid oligomers with a certain degree of polymerization under light or heating conditions. The conjugated linoleic acid oligomers can in-situ passivate the grain boundaries of the perovskite film, thereby simultaneously improving the light stability and energy conversion efficiency of the perovskite solar cell.

[0107] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a perovskite solar cell, characterized in that: The following steps are involved: Dissolving conjugated linoleic acid and / or conjugated linoleic acid low-polymerization-degree derivatives and perovskite materials in a solvent to obtain a perovskite precursor solution, The perovskite precursor solution is coated on the surface of the substrate to prepare the perovskite active layer.

2. The method for preparing a perovskite solar cell according to claim 1, characterized in that: The perovskite precursor solution includes the conjugated linoleic acid low-polymerization-degree derivative, and the degree of polymerization of the conjugated linoleic acid low-polymerization-degree derivative is less than or equal to 300.

3. The method for preparing a perovskite solar cell according to claim 1, characterized in that: The added amount of conjugated linoleic acid and / or conjugated linoleic acid low-polymerization-degree derivative in the solvent is (5-20) μL / mL.

4. The method for preparing a perovskite solar cell according to claim 1, characterized in that: In the step of preparing the perovskite active layer, the perovskite precursor solution is spin-coated onto the surface of the substrate, the spin-coating speed is 1000 rpm to 5000 rpm, and the spin-coating time is 10s to 30s.

5. The method for preparing a perovskite solar cell according to claim 1, characterized in that: After the perovskite precursor solution is coated on the surface of the substrate, it is also subjected to annealing treatment.

6. The method for preparing a perovskite solar cell according to claim 4, characterized in that: The annealing temperature is 100°C to 105°C, and the annealing time is 20min to 40min.

7. The method for preparing a perovskite solar cell according to claim 1, characterized in that: The substrate comprises an electron transport layer, and a perovskite active layer is prepared on the surface of the electron transport layer.

8. The method for preparing a perovskite solar cell according to claim 1, characterized in that: The substrate comprises a hole transport layer, and a perovskite active layer is prepared on the surface of the hole transport layer.

9. A perovskite solar cell prepared by the method for preparing a perovskite solar cell according to any one of claims 1 to 7.

10. The perovskite solar cell according to claim 9, characterized in that: The perovskite solar cell comprises, from bottom to top, a transparent conductive oxide layer, an electron transport layer, a perovskite active layer prepared by the preparation method according to any one of claims 1 to 8, a hole transport layer and a metal back electrode; or, The perovskite solar cell comprises, from bottom to top, a transparent conductive oxide layer, a hole transport layer, a perovskite active layer prepared by any preparation method according to claims 1 to 8, an electron transport layer and a metal back electrode.